Maslahah Najmuddin Al-Thufi: A Framework for Fintech Benefit Realization in Indonesia - Hasan, Nugraha; Abubakar, Achmad; Haddade, Hasyim; Kurniati, Kurniati; Nurjannah, Nurjannah; Sabbar, Sabbar Dahham (IAIN Manado, 2024)
This study explores the concept of maslahah, according to Najmuddin Al-Thufi, as a realization of fintech development in Indonesia. Najmuddin Al-Thufi developed a theory of maslahah that emphasizes flexibility and adaptability to dynamic socio-economic contexts. This study integrates the theory with the development of fintech in Indonesia. This descriptive and qualitative research provides a more comprehensive picture of the concept of maslahah at-Thufi and the phenomenon of fintech in detail and in-depth and using a phenomenological approach. Data sources come from secondary data from books and relevant and reliable journals related to the discussion of Maslahah Najmuddin at-Thufi and fintech. The results showed that applying Najmuddin al-Thufi's maslahah concept to the development of fintech in Indonesia can be implemented for effective regulation and support the growth of fintech in an inclusive, safe, and equitable manner. The maslahah principle, which focuses on the public good, can deal with challenges such as consumer protection, data security, financial inclusion, and business ethics. By applying this principle, regulations can be more adaptive and responsive to technological dynamics, ensuring that the real benefits to society are always prioritized in every regulatory decision.